EKSPLORASI KETERAMPILAN SOSIAL MELALUI PEMBELAJARAN BAHASA ARAB DI LINGKUNGAN PENDIDIKAN ANAK USIA DINI - Khairanis, Retisfa; Aldi, Muhammad (PT Rizkarya Cendekia Pustaka, 2025)
This research aims to explore early childhood social skills through Arabic language learning in an early childhood education (ECE) setting. The scope of the research includes observing and analyzing children's social interactions during the Arabic language learning process and its impact on their social skills development. The method used in this research is a qualitative approach with data collection techniques through observation, interviews with teachers, and group discussions with parents. The results showed that Arabic language learning conducted interactively and collaboratively can improve children's social skills, such as the ability to communicate, collaborate, and empathy. Children who engaged in group activities, such as role-play and discussion, showed significant improvements in their ability to interact with peers. In addition, the use of Arabic in a social context helps children understand the norms and values prevailing in society. The conclusion of this research is that Arabic language learning serves not only as a means of communication, but also as a means to develop important social skills for early childhood. Therefore, it is important for educators to integrate social activities in Arabic language learning in ECD in order to facilitate children's holistic development. This research provides new insights into the role of Arabic language in early childhood education and the importance of learning environments that support social interaction. Keywords: Exploration; Social Skills; Arabic Language; Early Childhood Education